Odpowiedź :
Odpowiedź:
[tex]\huge\boxed{\boxed{x\in(-\infty;\frac{1}{2})\cup(4;+\infty)}}[/tex]
Szczegółowe wyjaśnienie:
[tex]x(2x-1)+4>8x\\\\2x^2-x-8x+4>0\\\\2x^2-9x+4>0\\\\a=2, \ b=-9, \ c=4 \ (z \ postaci \ y=ax^2+bx+c)\\\\\Delta=b^2-4ac\Rightarrow(-9)^2-4\cdot2\cdot4=81-32=49\\\\\sqrt{\Delta}=\sqrt{49}=7\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\Rightarrow\frac{-(-9)-7}{2\cdot2}=\frac{9-7}{4}=\frac{2}{4}=\frac{1}{2}\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\Rightarrow\frac{-(-9)+7}{2\cdot2}=\frac{9+7}{4}=\frac{16}{4}=4\\\\x\in(-\infty;\frac{1}{2})\cup(4;+\infty)[/tex]
a > 0, ramiona paraboli są skierowane do góry
Odpowiedź:
x ∈ (-∞; ¹/₂) ∪ (4; +∞)
Szczegółowe wyjaśnienie:
[tex]x(2x-1)+4>8x\\\\2x^{2}-x+4-8x>0\\\\2x^{2}-8x-x+4 > 0\\\\2x(x-4) -(x-4) > 0\\\\(2x-1)(x-4) > 0\\\\M. \ zerowe:\\\\2x-1 = 0 \ \vee \ x-4 = 0\\\\x = \frac{1}{2} \ \vee \ x = 4\\\\a > 0, \ ramiona \ paraboli \ skierowane \ do \ gory\\\\\boxed{x \in (-\infty; \frac{1}{2}) \ \cup \ (4; +\infty)}[/tex]